Morphotype Classification Criteria and Influence of Sociocultural Factors on Perceived Shea Tree (Vitellaria paradoxa C.F. Gaertn) Natural Variation across Parklands in Benin - FRANCISCO MERINOSY, MICHEE FUSTELLE; Achigan-Dako, Enoch Gbenato; GNANGLE, Césaire; KASSA, Eugène; BOFFA, Jean Marc (My University, 2022)
Trait diversity is crucial in undertaking the domestication of useful species such as Vitellaria paradoxa which makes a significant contribution to the rural household economy in Africa. This study aims to document the criteria farmers use to distinguish shea trees; how they vary according to age, education level and sociolinguistic group; and their perception of trees’ abundance and production. We surveyed 405 respondents across shea parklands in Benin using a semi-structured questionnaire. We used the Kruskal-Wallis test to evaluate the influence of sociodemographic attributes on relative criteria citation frequency and principal components analysis to characterize farmers’ perception on morphotypes’ abundance, fruits, and butter yields. The five most cited criteria were fruit size (55.5%), tree fertility (15.40%), bark colour (10.51%), timing of production (5.38%), and pulp taste (3.42%). The citation frequency of criteria varied significantly depending on the sociodemographic factors considered. Trees having small fruit (‘Yanki’) were reported to be widespread and high fruit/nuts and butter producers. Farmers perceived five important traits with variable importance depending on the sociocultural factors studied. This finding is a key step toward the development of a shea improvement program that could focus on the morphotype Yanki reported to potentially be a high fruit and butter producer
Keywords: Vitellaria paradoxa; morphotypes; criteria; sociodemographic attributes; West Africa